The need of formative assessment: the assessment FOR learning - Shrestha, Roshana (Journal of General Practice and Emergency Medicine of Nepal, 2019)
A 59 years old female with a history of diabetes mellitus, diagnosed of breast cancer stage 4 is unhappy with her doctors including the oncologist, primary care physician, pulmonologist and endocrinologist (all board toppers). She is frustrated that her doctors doesn’t listen to her concern and orders new tests and prescribes new medication during each visit